What if firms adjust their debt-equity ratios toward a target range? - Pereira, Ricardo Buscariolli (2009)
We estimate optimal target-ranges of capital structure controlling for a series of firmspecific characteristics and accounting for the serial correlation that arises from the dynamic component of the leverage choice. Then, we empirically examine if firms adjust their leverages toward the estimated optimal ranges. Our analysis suggests that the observed behavior of firms is consistent with the notion of range-adjustment.